Impact of molasses quality on ethyl alcohol fermentation by the yeast saccharomyces cerevisiae - Sibanda, Mkhululi Benedict (Centre for Bioprocess Engineering Research, 2014)
The use of blackstrap cane molasses in industrial ethanol production is characterised by fluctuations in fermentation efficiency due to its compositional variation. Crucial to optimisation of ethanol production is thorough knowledge of the constituents and properties of molasses which affect fermentation, in order to implement measures to diminish negative and augment positive impacts. These include both major and minor constituents. According to literature, aspects of fermentation media which affect yeast fermentation include nutritional availability, the presence of trace elements and growth factors such as vitamins, without which yeast proliferation is inhibited. High osmotic pressures, found in VHG (very high gravity) fermentations, have a detrimental effect on the fermentation process. Additionally, elevated concentrations of inorganic salts and ionic strength in industrial fermentation media have been implicated in negatively affecting fermentation. Based on these limited literature findings, the study addressed the effect of three cation constituents of molasses (K+, Mg2+ and Na+), expressed in terms of overall concentration, osmotic pressure and ionic strength, on fermentation was investigated in molasses media and a sucrose-based media.